2022
DOI: 10.3390/min12030349
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects of Clay Minerals from the Baltic States for Industrial-Scale Carbon Capture: A Review

Abstract: Carbon capture is among the most sustainable strategies to limit carbon dioxide emissions, which account for a large share of human impact on climate change and ecosystem destruction. This growing threat calls for novel solutions to reduce emissions on an industrial level. Carbon capture by amorphous solids is among the most reasonable options as it requires less energy when compared to other techniques and has comparatively lower development and maintenance costs. In this respect, the method of carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 255 publications
(431 reference statements)
0
3
0
Order By: Relevance
“…Carbon dioxide (CO 2 ) interaction with water in material nanopores play an important role in carbon dioxide removal and sequestration. , For example, in geological sequestration, numerous investigations concluded that clay adsorbs a significant amount of CO 2 into clay interlayers. , In CO 2 removal via enhanced weathering, CO 2 forms carbonic acid that dissolves rock (e.g., basalt) and releases Ca 2+ and Mg 2+ . Geological minerals are also potential alternatives to more complex materials that often require significant chemical functionalization to ensure acceptable carbon capture performance. , Geological minerals have the distinct advantages of large surface area, high porosity, abundant basic sites, excellent thermal and chemical stability, and low cost .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) interaction with water in material nanopores play an important role in carbon dioxide removal and sequestration. , For example, in geological sequestration, numerous investigations concluded that clay adsorbs a significant amount of CO 2 into clay interlayers. , In CO 2 removal via enhanced weathering, CO 2 forms carbonic acid that dissolves rock (e.g., basalt) and releases Ca 2+ and Mg 2+ . Geological minerals are also potential alternatives to more complex materials that often require significant chemical functionalization to ensure acceptable carbon capture performance. , Geological minerals have the distinct advantages of large surface area, high porosity, abundant basic sites, excellent thermal and chemical stability, and low cost .…”
Section: Introductionmentioning
confidence: 99%
“…European Union Strategy for the Baltic Sea Region (EUSBSR) is a regional strategy that was approved by the European Council in 2009 [13][14][15][16][17]. It is the first of its kind in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their modification allows for the improvement of CO 2 adsorption capabilities even more. The prospects of the most widely available clay minerals in the Baltic States for large-scale CO 2 emission reduction and suitable alternative approaches for clay modification to improve CO 2 adsorption capacity can be found in review [66]. Recently, clay-containing MOF-composites have been studied for various purposes.…”
Section: Introductionmentioning
confidence: 99%